ANALISIS PERSEDIAAN ALAT PELENGKAP PADA PROSES PRODUKSI KAYU DENGAN METODE ECONOMIC ORDER QUANTITY (EOQ) - Irfan Saifudin; Moch Nuruddin (JURNAL REKAYASA SISTEM INDUSTRI, 2022)
Inventory control is one of the most important things for the company, because without proper and optimal inventory control the company will experience a problem in meeting production needs and consumer demand needs both in the form of goods and services produced by the company. a wood manufacturing company located in Gresik Regency. In the process of making products, problems often occur, namely the number of requests for complementary tools that are quite large and uncontrolled, it is necessary to have optimal inventory control. To minimize the inventory, Economic Order Quantity (EOQ) analysis can be used as a control or ordering tool for the company so that the ordering becomes optimal. From the results of calculations that have been carried out, the calculation shows that the relationship between the EOQ, Safety Stock, ROP, and Inventory methods of complementary tools for grinding grinding stones 8 INCH and grinding stones 4 x 1.2 mm is as follows: in the period September 2021 - July 20222 it shows that the purchase of complementary tools when the stock of 8 INCH grinding stones is 17 units and 4 x 1.2 mm grinding stones are 10 units, thus when ordering complementary tools are received with a Lead Time of 7 days for 8 INCH grinding stones and 4 days for 4 x 1.2 mm grinding stones, safety stock still remaining 7 units for the 8 INCH Grinding Stone and 5 units for the 4x1.2 mm Grinding Stone, while to avoid excess number of complementary tools in the warehouse, the optimal number of purchases of 8 INCH Grinding Stones and 4x1.2 mm Grinding Stones of 117 and 159 units. With calculations using the EOQ method, the total value of the supply of complementary tools for grinding grinding stones 8 INCH and grinding stones 4x1.2 mm is Rp. 469,041 da Rp. 253.968.